Comparative evaluation of genetic risk models of reproductive disorders caused by MTHFR, MTRR, MTR1 gene polymorphism. - Z. І. Rossokha; S. P. Kyriachenko; N. G. Gorovenko (Medičnì Perspektivi)
The scientific literature presents contradictory data about influence of folate metabolism genes polymorphism on development of risk of reproductive disorders. The aim of the study was to determine the role of MTHFR, MTRR, MTR1 gene polymorphism in the development of reproductive disorders by evaluation of genetic risk models of inheritance. 658 patients with reproductive disorders from all Ukrainian regions were examined. The data from population studies presented in the online resource (1000 genomes) served as comparison group. There were no reliable risk models for polymorphic variants of MTHFR gene. We identified 3 and 4 significant inheritance models for MTRR and MTR1 genes respectively. The best inheritance models were the dominant model for MTRR gene and the additive model for MTR1 gene. The polymorphic variants frequencies of the studied genes did not differ among men and women. Further analyse is necessary for evaluation of genetic polymorphism and intergenic interactions influence on reproductive disorders risk, taking into account folate metabolism indices and exogenous factors.